자가면역 호중구 감소증 1 예 - 부철수; Cheol Su Poo; 김지수; Ji Soo Kim; 조현장; Hyun Jang Cho; 양승호; Yang Seung Ho; 이헌직; Heon Jik Lee; 김두형; Du Hyung Kim; et al. (The Korean journal of medicine, 1998)
Autoimmune neutropenia is characterized by severe neutropenia with cell-bound neutrophil antibodies or circulating antibodies for neutrophils. Diagnosis of disease is made of the basis of the presence of antibodies for neutrophil. Corticosteroid or rhG-CSF have been reported to be effective in some patients. Recently we experienced one case of autoimmune neutropenia patient who was admitted to our hospital in 1997 because of stomach cancer and degenerative joint disease. She had severe neutropenia without underlying autoimmune disease. And cell-bound neutrophil antibodies were detected by indirect immunofluorescence test. Treatments with rhG-CSF and steroid result in transient improvement of neutropenia and subtotal gastrectomy was done successfully. We herein report one case of autoimmune neutropenia patient, to our best knowledge, the first report in Korea, with a brief review of literature.